(untitled) (Archive of Oncology, 2024)
A potential complication that affects a patient’s quality of life is breast cancer - related lymphedema (BCRL). Due to lymphatic system failure brought on by breast cancer treatment, it is secondary lymphedema. This literature review examines 50 articles that are connected to BCRL. The reason for the correction is an error in the paper’s Conclusion which occurred due to an oversight by the Editorial Team during preparation for electronic publication.